2010
DOI: 10.3390/molecules15096423
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Indigo Naturalis on Tumor Necrosis Factor-α-Induced Vascular Cell Adhesion Molecule-1 Expression in Human Umbilical Vein Endothelial Cells

Abstract: The use of indigo naturalis to treat psoriasis has proved effective in our previous clinical studies. The present study was designed to examine the anti-inflammatory effect of indigo naturalis in primary cultured human umbilical vein endothelial cells (HUVECs). Pretreatment of cells with indigo naturalis extract attenuated TNF-α-induced increase in Jurkat T cell adhesion to HUVECs as well as decreased the protein and messenger (m)RNA expression levels of vascular cell adhesion molecule-1 (VCAM-1) on HUVECs. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In addition, in vitro studies demonstrated that indigo naturalis could regulate differentiation and proliferation of epidermal keratinocytes (Lin et al, 2009a), inhibit proinflammatory responses of neutrophils (Lin et al, 2009b), and suppress tumor necrosis factor-␣-induced vascular cell adhesion molecule-1 expression in endothelial cells (Chang et al, 2010). The current The same treatment as for cytotoxicity evaluation was conducted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, in vitro studies demonstrated that indigo naturalis could regulate differentiation and proliferation of epidermal keratinocytes (Lin et al, 2009a), inhibit proinflammatory responses of neutrophils (Lin et al, 2009b), and suppress tumor necrosis factor-␣-induced vascular cell adhesion molecule-1 expression in endothelial cells (Chang et al, 2010). The current The same treatment as for cytotoxicity evaluation was conducted.…”
Section: Discussionmentioning
confidence: 97%
“…In traditional Chinese medicine, indigo naturalis possesses the properties of "clearing away heat, detoxicating, removing blood heat and ecchymoses, purging live-fire and arresting convulsion", and it can be used for antipyretic, anti-inflammatory, antiviral, antimicrobial, and detoxifying purposes (Mak et al, 2003;Fatima et al, 2007). Prior to the advent of antibiotic and steroid therapies, indigo naturalis was employed to treat high fever in infectious sickness, infantile convulsions, epilepsy, aphtha, mumps, pharyngitis, tonsillitis, gingivitis, periodontitis, or inflammatory skin diseases, such as carbuncle, furuncle, erysipelas, and eczema (Chang et al, 2010). Based on these known therapeutic effects, indigo naturalis may possess antioxidant properties or a protective effect against 0378-8741/$ -see front matter © 2011 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…Realgar, indigo naturalis, savia miltiorrhiza and radix pseudostellariae are clinically active antitumor compounds (15)(16)(17)(18). In 2006, the Phase II Clinical Trials Cooperative Group of China reported a similar curative effect between the administration of RA and CRNIT treatment in patients with incipient APL (19).…”
Section: Discussionmentioning
confidence: 99%
“…Indigo naturalis has also been shown to exert anti-inflammatory effect by inhibiting the adhesion of lymphocytes and reducing the c-jun activation and VCAM-1 gene expression of human vascular endothelial cells [30]. These results might contribute significantly to the reduced infiltration of lymphocytes in psoriatic lesions after the clinical treatment with indigo naturalis [32].…”
Section: Discussionmentioning
confidence: 94%